Some elements of economic efficiency of biological treatment to combat corn borer (Ostrinia nubilalis Hbn) in the conditions of Transylvania - Felicia Mureşanu; Voichiţa Haş; Mircea Ignea (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
The paper is a synthesis of the results obtained during 1998-2010, on the effectiveness of biological (Trichogramma spp.) and chemical treatments (different insecticides) in reducing the attack of Ostrinia nubilalis Hbn. to the corn genotypes created at The Agricultural Research and Development Station Turda. Among Trichogramma species used, a good efficacy in reducing attack of Ostrinia nubilalis was presented by T. maidis (80.0 %) and T. evanescens (78.0 %) - 3 applications. The applications with these species of Trichogramma to maize crops should be done at a distance of 6-7 m / row and between rows, in order to allow a uniform dispersion and a high degree of parasitizing eggs of corn borer. The biological treatments with T. maidis made to corn hybrids created at SCDA Turda, had reduced significantly the corn borer attack, recording production increases from 4.0 to 11.0 %. The basic conditions for achieving high efficiency in reducing the attack of Ostrinia nubilalis, with Trichogramma spp. are: conducting applications at optimal moment and ensuring optimum densities correlated with the density of the pest and chemicals used (Decis Mega 50 EW, Calypso 480 SC) had reduced the attack frequency significantly and very significantly, their efficacy in this regard was between 87-90 %. From the analysis performed through the economic effect of biological and chemical treatments to combat corn borer (Ostrinia nubilalis) resulted certain economic advantages using the method of biological control with Trichogramma spp., both in terms of reducing costs per hectare and the production growth produced. Thus, the species of this entomophage used, Trichogramma spp., constitutes in a way a "new generation of biological insecticides", that does not pollute and is used to combat the over 500 species of pests in the order Lepidoptera.
Keywords: 330; Trichogramma spp.; Ostrinianubilalis Hbn.; biological treatments; economic efficiency